Integrated biomarker responses as environmental status descriptors of a coastal zone (São Paulo, Brazil) - Seabra Pereira, Camilo Dias; Laura Martin-Diaz, Maria; Zanette, Juliano; Cesar, Augusto; Choueri, Rodrigo Brasil; de Souza Abessa, Denis Moledo [UNESP]; Catharino, Marilia Gabriela M.; Vasconcellos, Marina B. A.; Dias Bainy, Afonso Celso; Pereira Moreira de Sousa, Eduinetty Ceci; Angel Del Valls, Tomas (Academic Press Inc. Elsevier B.V., 2011)
São Paulo state (Brazil) has one of the most overpopulated coastal zones in South America, where previous studies have already detected sediment and water contamination. However, biological-based monitoring considering signals of xenobiotic exposure and effects are scarce. The present study employed a battery of biomarkers under field conditions to assess the environmental quality of this coastal zone. For this purpose, the activity of CYP 450, antioxidant enzymes, DNA damage, lipid peroxidation and lysosomal membrane were analysed in caged mussels and integrated using Factorial Analysis. A representation of estimated factor scores was performed in order to confirm the factor descriptions characterizing the studied areas. Biomarker responses indicated signals of mussels' impaired health during the monitoring, which pointed to the impact of different sources of contaminants in the water quality and identified critical areas. This integrated approach produced a rapid, sensitive and cost-effective assessment, which could be incorporated as a descriptor of environmental status in future coastal zones biomonitoring. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Biomarkers; Biomonitoring; Caged mussels; Multivariate analysis; São Paulo coast